2022
DOI: 10.1007/s41999-022-00735-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early postoperative factors on changes in skeletal muscle mass after esophagectomy in older patients with esophageal cancer

Abstract: Background Loss of skeletal muscle mass, measured by the skeletal muscle mass index (SMI), after esophagectomy negatively impacts prognosis. However, the information to develop novel supportive care options for preventing loss of skeletal muscle mass is limited. The purpose of this retrospective cohort study was to investigate the impact of early postoperative factors on change in SMI 4 months after curative esophagectomy in older patients with esophageal cancer. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Terefore, in older patients with esophageal cancer, postoperative progression of frailty with SMM 4 months after surgery may impact the recovery status of SMM 12 months after surgery independent of preoperative characteristics. Te most recent study reported that the loss of SMI 4 months after surgery was afected by the decline in quadriceps muscle strength in the frst month after surgery in older patients with esophageal cancer [37]. Additionally, a previous study reported that esophageal cancer patients with low physical activity after discharge had a higher percentage loss of SMM 6 months after surgery than those with high physical activity [38].…”
Section: Discussionmentioning
confidence: 98%
“…Terefore, in older patients with esophageal cancer, postoperative progression of frailty with SMM 4 months after surgery may impact the recovery status of SMM 12 months after surgery independent of preoperative characteristics. Te most recent study reported that the loss of SMI 4 months after surgery was afected by the decline in quadriceps muscle strength in the frst month after surgery in older patients with esophageal cancer [37]. Additionally, a previous study reported that esophageal cancer patients with low physical activity after discharge had a higher percentage loss of SMM 6 months after surgery than those with high physical activity [38].…”
Section: Discussionmentioning
confidence: 98%